Commuting and Sickness Absence - Olga Lorenz; Laszlo Goerke (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2015)
Commuting is an important and growing component of workers daily life and demands a lot of time. Given the importance of commuting, it is crucial to understand its consequences for different aspects of individual labour supply. In this paper, we focus on the causal effect of commuting on sickness absence from work using German panel data. According to theory, the effect of commuting on the number of workers absence days may be positive or negative. Empirical tests of this effect are not standard, due to reverse causation and lack of good control variables. To address reverse causation, estimates of commuting on absenteeism are derived using changes in commuting distance for workers who stay at the same workplace and who have the same residence during the period of observation. Keeping the workers employer and residence constant allows us to address endogeneity of commuting distance. Our results show that employees, who commute long distances (more than 50 kilometres), are absent more often than comparable employees with shorter commutes.
Keywords: I10; J22; R40; 330